Developing Reading Comprehension Test for The First Semester Students of English Department - Hanafi, Hanafi (ELLITE, 2016)
This research is inspired by the facts that in the previous research, for doing researches, some researchers have to make themselves the instruments they need for their research. The instruments especially test available in the market are usually made based on general criteria. That is why they can not fulfill the need of research since it must be specific depending on the condition of each respondent. The purpose of this research is to develop a reading comprehension test items which fulfill the criteria of â€œgood testâ€. The test materials are taken from some sources and developed using Azwar Model. The evaluation on the test from the result of tryout shows that the test made by the researcher has fulfilled the criteria of valid, reliable and practical.Keywords: reading comprehension, test, valid, and reliable, practical